Clinical methods and practicum in speech-language pathology - Hegde, M. N. (Mahabalagiri N.), 1941-; Kuyumjian, Katrina (San Diego, CA : Plural Publishing, Inc., 2020)
The sixth edition of Clinical Methods and Practicum in Speech-Language Pathology remains a vital resource for students in speech-language pathology who are about to begin their clinical practicum. The book is divided into two major sections: clinical practicum and clinical methods in speech language pathology. These sections provide coverage of the structural and functional aspects of clinical practicum in a variety of settings. The book emphasizes clinical practicum is an exciting learning experience. The students will understand what is expected of them in each setting and what they can expect from their clinical supervisors. The book also gives an overview of treatment methods that apply across disorders. With this book, students will be better prepared to meet the exciting and yet often challenging task of providing ethical and effective services to children and adults with communication disorders. Clinical supervisors may find the book helpful in understanding their own roles and responsibilities better so that they can create a productive and exciting clinical practicum experience for their student clinicians. Clinical Methods and Practicum in Speech-Language Pathology offers a single and comprehensive source of information that will help establish clear expectations for both student clinicians and the clinical supervisors. New to the Sixth Edition New coauthor, Katrina Kuyumjian A new chapter with an overview of treatment procedures that apply across disorders of communication Revised section on clinical methods to include updated information on the current ASHA guidelines on clinical practicum; current legal and professional requirements regarding clinical practicum in educational settings; new and expanded information on assessment, target behaviors, and treatment strategies for all disorders of communication Updated and expanded references throughout Key Features Chapter Outlines open each chapter and provide a summary of the key topics An end-of-book glossary allows readers to easily find and define important terms or concepts Bulleted and boxed information for easy access.
Clinical practicum in speech-language pathology -- Organization of clinical practicum -- The conduct of the student clinician -- The supervisor and the student clinician -- Working with clients -- Multicultural issues in clinical practicum -- Effective treatment procedures for all disorders -- Target behaviors across disorders -- Treatment in speech-language pathology : core techniques -- Controlling undesirable behaviors -- Maintenance of target behaviors.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 6, 2019).
Master record variable field(s) change: 050
Keywords: Speech therapy -- Study and teaching; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Speech therapy -- Study and teaching; Electronic books